Changes in hemodynamic response function components reveal specific changes in neurovascular coupling in type 2 diabetes - Duarte, João Valente; Guerra, Catarina; Moreno, Carolina; Gomes, Leonor; Castelo-Branco, Miguel (Frontiers in Physiology, 2023)
Type 2 Diabetes Mellitus (T2DM) is a metabolic disease that leads to multiple vascular complications with concomitant changes in human neurophysiology, which may lead to long-term cognitive impairment, and dementia. Early impairments of neurovascular coupling can be studied using event related functional magnetic resonance imaging (fMRI) designs. Here we aimed to characterize changes in the hemodynamic response function (HRF) in T2DM to probe components from the initial dip to late undershoot. We investigated whether the HRF morphology is altered throughout the brain in T2DM, by extracting several parameters of the fMRI response profiles in 141 participants (64 patients with T2DM and 77 healthy controls) performing a visual motion discrimination task. Overall, patients revealed significantly different HRFs, which extended to all brain regions, suggesting that this is a general phenomenon. The HRF in T2DM was observed to be more sluggish, with higher peak latency, and lower peak amplitude, relative slope to peak, and area under the curve. It also showed a pronounced initial dip, suggesting that initial avidity for oxygen is not compensated for, and an absent or less prominent but longer undershoot. Most HRF parameters showed higher dispersion and variability in T2DM. In sum, we provide a definite demonstration of an impaired hemodynamic response function in the early stages of T2DM, following a previous suggestion of impaired neurovascular coupling. The quantitative demonstration of significantly altered HRF morphology in distinct response phases suggests alteration of distinct physiological mechanisms related to neurovascular coupling which should be considered in the future to potentially halt the deterioration of the brain function in T2DM.